Evaluation of Urinary Excretion and Renal Clearance of Deferiprone, Creatinine, Iron and Zinc in Human - ABBAS, MATEEN; NAWAZ, RAKHSHANDA; SHAHID, MUHAMMAD; NAWAZ, MUHAMMAD; ALIM, MUHAMMAD; RAFIQUE ASI, MUHAMMAD (Asian Journal of Chemistry, 2010)
Iron chelators are used in medicine to protect patients from the consequences of iron overload and iron toxicity. Deferiprone (1,2-dimethyl- 3-hydroxypyrid-4-one), which belongs to the family of α-ketohydroxypyridines, is an oral iron chelator that is used clinically, mainly in patients with thalassemia. The urinary excretion and renal clearance of deferiprone was investigated in 24 healthy male volunteers following oral administration of a single dose 500 mg. Concentration of deferiprone in plasma and urine was determined by high performance liquid chromatography, iron and zinc by atomic absorption spectrophotometer and the concentration of creatinine by chemistry analyzer. Total amount of deferiprone excreted in 24 h was 13.7 ± 1.24 mg. The renal clearance of endogenous creatinine was 0.90 ± 0.11 mL/min/Kg and deferiprone was 0.29 ± 0.04 mL/min/Kg being about one third of the filtration clearance. The renal excretory mechanisms involved glomerular filtration, excreting only 2.73 % of the oral dose of deferiprone through urine. Lower values of the deferiprone renal clearance than the GFR indicate that the excretion of the drug through kidneys involves glomerular filtration and extensive renal tubular back diffusion or reabsorption. The literature for excretion and renal clearance parameters of deferiprone is inadequate; however similarities and differences were both observed when the present findings were compared with the cited results.